2021
DOI: 10.1145/3439827
|View full text |Cite
|
Sign up to set email alerts
|

A Network Analysis of Twitter Interactions by Members of the U.S. Congress

Abstract: Usage of Twitter by politicians has become more prevalent in recent years, with a goal of influencing the electorate and public perception. We collect, explore, and analyze over 12 years of public Twitter interactions of U.S. senators and representatives. Using community detection algorithms on these interaction networks, and without considering the content of the tweets, we are able to infer the political affiliation of each member of Congress with up to 98.8% accuracy in the House and 94.1% accuracy in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…( 2021 ); Chamberlain et al. ( 2021 ) that suggest the mention networks to be reflective of cross-party interactions. One possible reason for this could be the nature of different interaction networks of Twitter.…”
Section: Discussionmentioning
confidence: 99%
“…( 2021 ); Chamberlain et al. ( 2021 ) that suggest the mention networks to be reflective of cross-party interactions. One possible reason for this could be the nature of different interaction networks of Twitter.…”
Section: Discussionmentioning
confidence: 99%
“…The technological affordance of social media offers politicians abundant opportunities to express their social identities and popularize party norms (Buccoliero et al, 2020). In addition, the highly homophilous nature of interactions among MoC on social media (Chamberlain et al, 2021) can make politicians highly cognizant of party identity and further encourage them to align their attitudes with the party (García-Sánchez et al, 2021). For these reasons, we propose the following hypothesis: H1: Democratic congressional members are more likely to promote mask-wearing than Republican congressional members on Twitter.…”
Section: Partisanship and Mask-wearing As A Group Normmentioning
confidence: 99%
“…Heere et al (2011), for example, found that interactions between individual members strongly influenced their perception of group-belonging, the formation of social identity, and support for associated organizations. In political settings, research has shown that politicians are more likely to co-sponsor a bill with in-group members (Neal, 2020) and interact with in-group members on social media (Chamberlain et al, 2021).…”
Section: Member Interactionsmentioning
confidence: 99%
“…"Twitter is the de facto social media platform for discussing politics online" (Chamberlain et al 2021). Twitter has been described as a political tool (Pérez-Curiel and Limón Naharro 2019; Redek and Godnov 2018) and as a political network (Conway and Wang 2015;Fernández Gómez et al 2018) as it represents a significant role in political communication campaigns (Alonso-Muñoz et al 2016;Usher 2018).…”
Section: Twitter the Political Network?mentioning
confidence: 99%
“…Twitter research on echo chambers has focused on interactions and content exposure, and the methods can vary, using digital trace data and self-reported data (Terren and Borge 2021). Political communication has been approached in Twitter studies in different research areas such as the use of the platform in determined events, its use by the public, and the use that political parties and politicians make of the microblogging network (Chamberlain et al 2021;Jungherr 2016).…”
Section: Twitter the Political Network?mentioning
confidence: 99%